Modal Analysis and Flow through Sectionalized Pipeline Gate Valve Using FEA and CFD Technique - Desejo Filipeson Sozinando; Bernard Xavier Tchomeni; Alfayo Anyika Alugongo (Journal of Engineering)
Sectionalized gate valves can reduce the volume of product released in the event of a buried pipeline failure or rupture. The risk of pipeline failure is a constant and common occurrence, and many factors can lead to pipeline incidents. In this paper, the free undamped vibration of the pipeline, sectionalized gate valve structure, and the dynamics of the fluid passing through the system are investigated. First and foremost, a modal analysis based on finite element analysis (FEA) is introduced as a fundamental linear dynamics analysis to provide insight into how a pipeline sectionalized gate valve structure may respond to different types of dynamic loading. Secondly, an implicit numerical analysis using computational fluid dynamics (CFD) is employed to describe physical quantities such as the flow velocity profiles at different stream positions and pressure fields at different points in a control volume. Through modal analysis, the effective mass factor shows the mass involved in each mode and helps identify modes with high potential to cause damage and prioritize efforts to address them. The CFD suggests that the sectionalized design of the gate valve leads to a strong vorticity of the fluid in the transversal direction of the flow and a decrease in efficiency due to pressure drop.